2014
DOI: 10.1007/s00221-014-4156-x
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery of locomotion with an additional load: actual load experience does not affect differences between physical and mental durations

Abstract: Motor imagery relies strongly on motor representations. Currently, it is widely accepted that both the imagery and execution of actions share the same neural representations (Jeannerod, Neuroimage 14:S103-S109, 2001). Comparing mental with actual movement durations opens a window through which to examine motor representations and how they relate to cognitive motor processes. The present experiment examined mental durations reported by participants standing upright who imagined walking either with or without an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…The first step of this investigation was to replicate the underproduction of imagined walking duration. Although multiple research groups independently found this pattern (Grechkin et al, 2010;Kunz et al, 2009;Munzert et al, 2015;Stevens, 2005), there are also studies in IMAGINED WALKING 7 which real and imagined walking times were comparable to each other (Bakker et al, 2007;Courtine et al, 2004;Fusco et al, 2014;Papaxanthis et al, 2002;Personnier et al, 2010;Schott & Munzert, 2007). Given this discrepancy in the literature, replication of the underproduction tendency would be crucial for the present study.…”
Section: Imagined Walkingmentioning
confidence: 95%
See 3 more Smart Citations
“…The first step of this investigation was to replicate the underproduction of imagined walking duration. Although multiple research groups independently found this pattern (Grechkin et al, 2010;Kunz et al, 2009;Munzert et al, 2015;Stevens, 2005), there are also studies in IMAGINED WALKING 7 which real and imagined walking times were comparable to each other (Bakker et al, 2007;Courtine et al, 2004;Fusco et al, 2014;Papaxanthis et al, 2002;Personnier et al, 2010;Schott & Munzert, 2007). Given this discrepancy in the literature, replication of the underproduction tendency would be crucial for the present study.…”
Section: Imagined Walkingmentioning
confidence: 95%
“…A number of studies have been carried out to investigate mental simulation of walking, and results from these studies are consistent with the general findings summarized above: In overt behavior, the time it IMAGINED WALKING 6 takes participants to imagine walking a given distance varies systematically as a function of the walked distance (and thus as a function of the time it takes them to physically walk the same distance; Bakker, de Lange, Stevens, Toni, & Bloem, 2007;Courtine, Papaxanthis, Gentili, & Pozzo, 2004;Decety, Jeannerod, & Prablanc, 1989;Fusco et al, 2014;Papaxanthis, Pozzo, Skoura, & Schieppati, 2002;Personnier, Kubicki, Laroche, & Papaxanthis, 2010;Plumert, Kearney, Cremer, & Recker, 2005;Saimpont, Malouin, Tousignant, & Jackson, 2012;Schott & Munzert, 2007); and in the brain, movement-related areas such as the premotor cortex, supplementary motor area, and cerebellum are commonly activated while participants perform real and imagined walking (Bakker et al, 2008;Hamacher et al, 2015;Hanakawa et al, 1999;Harada, Miyai, Suzuki, & Kubota, 2009;Jahn et al, 2004;la Fougère et al, 2010;Miyai et al, 2001;van der Meulen, Allali, Rieger, Assal, & Vuilleumier, 2014). However, one notable observation is that participants often underproduce imagined walking times relative to real walking times that they spend actually walking the same distances (Grechkin, Nguyen, Plumert, Cremer, & Kearney, 2010;Kunz et al, 2009;Munzert, Blischke, & Krüger, 2015;Stevens, 2005). The degree of underproduction can be substantial, making the imagined walking times as short as 59% of the corresponding real walking times (Stevens, 2005).…”
Section: Imagined Walkingmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor imagery refers to the mental rehearsal of movement from the first-person perspective in the absence of overt motor action (Jeannerod 1995;Madan & Singhal, 2012;Munzert et al, 2015;Munzert et al, 2009). Indications that this cognitive strategy can facilitate motor skill acquisition and enhance motor performance have made it a popular research area in recent years, with particular interest being directed to possible applications in both athletic and clinical settings.…”
Section: Introductionmentioning
confidence: 99%